Sodium transport by rat cortical collecting tubule. Effects of vasopressin and desoxycorticosterone. - Reif, M C (1986)
We have used rat cortical collecting tubules perfused in vitro to study the effects of antidiuretic hormone (ADH) and desoxycorticosterone (DOCA) on the unidirectional fluxes of sodium. We found that in the basal state, lumen-to-bath flux (Jlb) and bath-to-lumen flux (Jbl) of 22Na were approximately equal, 39.5 +/- 3.9 and 41.8 +/- 11.0 pmol X min-1 X min-1, respectively, resulting in no net flux. Addition of 100 microU/ml ADH to the bath produced a stable increase in Jlb to 58.3 +/- 4.7 pmol X min-1 X mm-1. Pretreatment of the animal with DOCA for 4 to 7 d (20 mg/kg per d) increased baseline Jlb to 81.6 +/- 8.7 pmol X min-1 X mm-1. Addition of ADH to a tubule from a DOCA-pretreated rat caused an increase in Jlb to 144.1 +/- 12.0 pmol X min-1 X mm-1 X Neither hormone had an effect on Jbl X Thus ADH produced a greater absolute and fractional increase in Jlb when the animal was pretreated with DOCA, and the ADH-induced increase over baseline was greater than the DOCA-induced increase. Both the ADH-and DOCA-induced stimulation of Jlb were completely abolished by 10(-5) M luminal amiloride, suggesting that the route of sodium transport stimulated by both hormones involves apical sodium channels. However, ADH and DOCA have very different time courses of action; ADH acted within minutes, while aldosterone and DOCA are known to require 90-180 min. The facilitating action of ADH on DOCA-induced stimulation of sodium transport may be important for maximal sodium reabsorption and for the ability to achieve a maximally concentrated urine.